Single Case Experience of Immunosuppressant Administration to Systemic Sclerosis-ILD Patients with Aspergilloma - Wilujeng Anggraini; Perdana Aditya Rahman (Indonesian Rheumatology Association, 2022)
Background: Systemic sclerosis (SSc) is a chronic autoimmune disease that still poses a great challenge to clinicians. SSc is characterized by immune dysregulation and progressive fibrosis that typically affects variable internal organ involvement such as lungs. Interstitial lung disease (ILD) is a common manifestation of SSc and a leading cause of death. The immunosuppressive drug is the main treatment to suppress the inflammation process in SSc. Case presentation: In this case we report a 40-year-old female to suffer ILD-SSc. According to High-Resolution Computed Tomography (HRCT) thorax, we found that it was interstitial lung disease with aspergilloma. She got methylprednisolone 3x8 mg and azathioprine 2x50 mg. At the end of the treatment, the patient showed improvement in her clinical condition and showed no worsening condition in the HRCT evaluation for her fungal aspergilloma. Conclusion: Systemic sclerosis (SSc) is a rare autoimmune disease involving the skin and internal organs. The immunosuppressive agent is still the drug of choice for most autoimmune diseases. Immunosuppressive may promote fungal growth and have been associated with increased risk in most serious fungal diseases including aspergilloma.